1999
DOI: 10.1073/pnas.96.23.13336
|View full text |Cite
|
Sign up to set email alerts
|

Increased thrombin responsiveness in platelets from mice lacking glycoprotein V

Abstract: A role for glycoprotein (GP)V in platelet function has been proposed on the basis of observations that GP V is the major thrombin substrate on intact platelets cleaved during thrombin-induced platelet aggregation, and that GP V promotes GP Ib-IX surface expression in heterologous cells. We tested the hypotheses that GP V is involved in thrombin-induced platelet activation, in GP Ib-IX expression, and in other platelet responses by generating GP V null mice. Contrary to expectations, GP V ؊͞؊ platelets were nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 51 publications
9
98
1
Order By: Relevance
“…61,63,69 Apart from GP Ibα, GP V may also be involved in this scenario, since it is a prominent α-thrombin substrate and GP V -/-mice display enhanced platelet sensitivity to low doses of thrombin leading to in vivo increased thrombogenesis and embolus formation. 70,71 It has been suggested that proteolysis of GP V by α-thrombin reveals the ability of GP Ibα to act as a thrombin ligand and induce stimulatory responses. 72 Despite recognizing that an intact GP Ib/IX/V complex may be required for optimal thrombin responsiveness, there is little doubt that PARs are sufficient to activate platelets and account for most, if not all, of the thrombin-induced signaling.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…61,63,69 Apart from GP Ibα, GP V may also be involved in this scenario, since it is a prominent α-thrombin substrate and GP V -/-mice display enhanced platelet sensitivity to low doses of thrombin leading to in vivo increased thrombogenesis and embolus formation. 70,71 It has been suggested that proteolysis of GP V by α-thrombin reveals the ability of GP Ibα to act as a thrombin ligand and induce stimulatory responses. 72 Despite recognizing that an intact GP Ib/IX/V complex may be required for optimal thrombin responsiveness, there is little doubt that PARs are sufficient to activate platelets and account for most, if not all, of the thrombin-induced signaling.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Precipitated, GTP-bound Rap1B was separated by SDS-PAGE on 10 -20% acrylamide gradient gels, transferred to nitrocellulose, and identified by immunoblotting with a specific polyclonal antibody. Intracellular Ca 2ϩ concentration was evaluated using Fura-2-loaded platelets and calculated as described under "Experi- GPIb-IX-V on the platelet surface, and this interaction may contribute to platelet activation (33)(34)(35)(36)(37)(38). We therefore examined the role of GPIb-IX-V in thrombin-induced activation of Rap1B.…”
Section: Role Of Gpib-ix-v In the Adp-independent Activation Of Rap1bmentioning
confidence: 99%
“…This represents a high affinity receptor for thrombin, and a mounting body of evidence indicates that it may contribute to the activation of platelets (32)(33)(34)(35)(36)(37). It has been known for years that platelets from patients affected by the Bernard-Soulier syndrome, which lack GPIb-IX-V, show impaired response to thrombin (38).…”
mentioning
confidence: 99%
“…These two genes share the same genomic structure and are adjacent to each other, consistent with a tandem gene duplication event. GP5 encodes a subunit of the GP1b-V-IX receptor that binds von Willebrand factor and is important in platelet aggregation (Roth et al 1996;Gurney et al 2002), and it may act to negatively regulate the response of the activated receptor (Ramakrishnan et al 1999). We have shown that LRRC15 also encodes a transmembrane glycoprotein, expressed at the leading edge of migrating cells.…”
Section: (B) Activation Of Lrrc15 Upstream Sequences By Ews-wt1(+kts)mentioning
confidence: 99%